2019
DOI: 10.1590/1678-4685-gmb-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape of head and neck squamous cell carcinomas in a South Asian population

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer type globally and contributes significantly to burden of disease in South Asia. In Pakistan, HNSCC is among the most commonly diagnosed cancer in males and females. The increasing regional burden of HNSCC along with a unique set of risk factors merited a deeper investigation of the disease at the genomic level. Whole exome sequencing of HNSCC samples and matched normal genomic DNA analysis (n=7) was performed. Significant somatic sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Regarding the risk of bias evaluated by Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data, 18 studies were classified as having a low risk of bias, 27,29,34,35,37–45,49–51,54,55 and the others 15 were classified as having a moderate risk of bias 23–26,28,30–33,36,46–48,52,53 . The summary of each study's risk of bias assessment is in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the risk of bias evaluated by Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data, 18 studies were classified as having a low risk of bias, 27,29,34,35,37–45,49–51,54,55 and the others 15 were classified as having a moderate risk of bias 23–26,28,30–33,36,46–48,52,53 . The summary of each study's risk of bias assessment is in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, human papillomavirus (HPV) infection is a well-recognized factor, in addition to smoking and alcohol for SCCHN in Western countries. A study conducted in the Pakistani population with HPV-OSCC showed variation in driver genes mutation, including FGFR2 , ARID2, ALK , MLL3 , MYC, and ASNS, compared to dysregulated FGFR3 , E2F1 , and TRAF3 in HPV+ tumors [ 25 ]. In the current study, we did not evaluate the HPV status in our samples; however, some samples in a previous study [ 7 ] showed positivity for p16 or HPV in situ hybridization, indicating that HPV status might lead to differences in immune cell profiles as well as mutational landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…The responders also showed overexpression of ASNS ( 13 ). However, high expression of this gene is indispensable for oral SCC progression ( 77 ) and adaptation to nutrient deprivation and hypoxia ( 78 ), and may inhibit apoptosis. The other two genes, Nrf2 and Itga6, known to be promoting factors of chemoresistance, are overexpressed in the non-responders ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%